The international debt crisis and the banks - Otmar Emminger (Intereconomics, 1985)
When the international debt crisis broke in 1982 it appeared for a time that the crisis might engulf the international banking system. What part did the banks play in the creation of the problem? What was their role in overcoming the crisis? Dr. Otmar Emminger, former President of the Deutsche Bundesbank, answers these questions and names the consequences the crisis will have on the international banking industry.
Keywords: 330; Banking